The Alternative Route to Heme in the Methanogenic Archaeon Methanosarcina barkeri. (23rd January 2014) - Kühner, Melanie; Haufschildt, Kristin; Neumann, Alexander; Storbeck, Sonja; Streif, Judith; Layer, Gunhild
Abstract : In living organisms heme is formed from the common precursor uroporphyrinogen III by either one of two substantially different pathways. In contrast to eukaryotes and most bacteria which employ the so-called "classical" heme biosynthesis pathway, the archaea use an alternative route. In this pathway, heme is formed from uroporphyrinogen III via the intermediates precorrin-2, sirohydrochlorin, siroheme, 12, 18-didecarboxysiroheme, and iron-coproporphyrin III. In this study the heme biosynthesis proteins AhbAB, AhbC, and AhbD from Methanosarcina barkeri were functionally characterized. Using an in vivo enzyme activity assay it was shown that AhbA and AhbB (Mbar_A1459 and Mbar_A1460) together catalyze the conversion of siroheme into 12, 18-didecarboxysiroheme. The two proteins form a heterodimeric complex which might be subject to feedback regulation by the pathway end-product heme. Further, AhbC (Mbar_A1793) was shown to catalyze the formation of iron-coproporphyrin III in vivo . Finally, recombinant AhbD (Mbar_A1458) was produced in E. coli and purified indicating that this protein most likely contains two [4Fe-4S] clusters. Using an in vitro enzyme activity assay it was demonstrated that AhbD catalyzes the conversion of iron-coproporphyrin III into heme.